Indications, feasibility and outcome of robotic retroperitoneal lymph node dissection for metastatic testicular germ cell tumours - Carsten-Henning Ohlmann (Nature Portfolio, 2021)
Abstract Data on robotic retroperitoneal lymph node dissection (R-RPLND) for metastatic testicular germ cell tumours (mTGCTs) are scarce and the use of R-RPLND itself is still under debate. The aim of our study was to evaluate the indications, feasibility and outcomes of R-RPLND, with special emphasis on differences between primary R-RPLND (pR-RPLND) and post-chemotherapeutic R-RPLND (pcR-RPLND) in mTGCTs. We retrospectively analysed the data of patients who underwent R-RPLND for mTGCT between November 2013 and September 2019 in two centres in Germany. Indications, operative technique, intra- and postoperative complications and oncologic outcome were analysed. Twenty-three mTGCT patients underwent R-RPLND (7 pR-RPLND, 16 pcR-RPLND). For pR-RPLND versus pcR-RPLND, median time of surgery was 243 min [interquartile range (IQR) 123–303] versus 359 min (IQR 202–440, p = 0.154) and median blood loss 100 mL (IQR 50–200) versus 275 mL (IQR 100–775, p = 0.018). Intra- and postoperative complications were more frequent in pcR-RPLND (pcR-RPLND: intra/post: 44%/44%; pR-RPLND: intra/post: 0%/29%). However, these were only statistically significant in the case of intraoperative complications (intra: p = 0.036, post: p = 0.579). Intraoperative complications (n = 7), conversions (n = 4) and transfusions (n = 4) occurred in pcR-RPLND patients only. After a median follow-up of 16.3 months (IQR 7.5–35.0) there were no recurrences or deaths. R-RPLND displays a valuable, minimally invasive treatment option in mTGCT. However, R-RPLND is challenging and pcR-RPLND especially bears a considerable risk of complications. This operation should be limited to patients with an easily accessible residual tumour mass and to surgeons experienced in robotic surgery and TGCT treatment.